Effect of Breastfeeding and Serum Zinc Levels on Childhood Recurrent Tonsillopharyngitis - Bozkurt, Hayrunnisa Bekis (International Journal of Child Health and Nutrition, 2019)
Aim: To evaluate serum zinc levels and breast milk intake in pediatric patients with recurrent tonsillopharyngitis Material Method: 40 pediatric patients who were admitted to our polyclinics with the diagnosis of tonsillopharyngitis diagnosed as ≥ 7 times a year were included in Group 1; 40 healthy children who applied to the outpatient clinic for routine control in the same period were defined as Group 2. Serum zinc, blood parameters, C-reactive protein (CRP) values were studied from all patients. Patient complaints, breastfeeding time, and family history were questioned. Results: There was no significant difference between the groups in terms of Hemaoglobin(Hb), hematocrit(Hct), white blood cell count(WBC), platelet count(Plt), mean platelet volume(MPV) and CRP values were significantly higher in the patient group (p=0.001). Serum zinc levels were significantly lower in Group 1 than Group 2 (p=0.000; p <0.05). There was no significant difference between the groups regarding the duration of breastfeeding (p=0.086; p> 0.05). Conclusion: Our study showed that zinc deficiency may play a role in the etiopathogenesis of recurrent tonsillopharyngitis. Zinc supplementation may be recommended for children with recurrent tonsillopharyngitis There is a need for further studies to be done in larger population related to zinc levels in mother's milk content, serum zinc levels in mothers and zinc deficiency.